CONFLICT MANAGEMENT IN THE TRANSFORMATION OF EDUCATIONAL ORGANIZATIONS: UNDERSTANDING THE ROLE OF LEADERSHIP AND ORGANIZATIONAL CULTURE - Ariatpi, Fina; Marlina, Lenny (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Complex conflict dynamics often occur in educational institutions. Good leadership and a supportiveorganizational culture can help manage conflict during the transformation process. The aim of thisresearch is to study how organizational culture and leadership play an important role in handlingconflict during the transformation process of educational organizations. In collecting data, thisresearch used in-depth interviews , document analysis, and participant observation. Schoolprincipals, teachers and education staff are respondents who are directly involved in the transformationprocess. The thematic method was used to analyze the data to find conflict patterns, leadershiproles, and the effects of culture on the organization. The research results show that leadership that isvisionary and focuses on problem solving, as well as building openness in communication has a veryimportant role in managing conflict. A culture in the educational environment that supports theprogress of educators and education personnel, as well as collaboration between all stakeholders cancreate a harmonious environment. Where conflict is considered a process that must be gonethrough in reaching a mutual agreement, not as a division that threatens the harmony of educationalinstitutions.